2010
DOI: 10.1016/j.resmic.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Ciliates rapidly enhance the frequency of conjugation between Escherichia coli strains through bacterial accumulation in vesicles

Abstract: The mechanism underlying bacterial conjugation through protozoa was investigated. or bacteria had no effect on conjugation frequency. Co-localization of green fluorescent protein-expressing E. coli and PKH67-vital stained E. coli was observed in the same ciliate vesicles, suggesting that both donor and recipient bacteria had accumulated in the same vesicle. Kanamycin-resistant Escherichia coliIn this study, the conjugation frequency of bacteria was found to be significantly higher in vesicles purified from cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 40 publications
1
40
1
Order By: Relevance
“…We have previously found that a mixed culture of Escherichia coli with Tetrahymena ciliates could prove beneficial in gene exchange between the bacteria (Matsuo et al, 2010;Oguri et al, 2011). Since the gene exchanges significantly decline in the presence of phagocytosis inhibitor (latrunculin B), they appear to occur by conjugation via bacterial uptake following accumulation in ciliate vesicles (Matsuo et al, 2010). Thus, our data clearly indicate that ciliate vacuoles provide benefits, via gene exchanges, to the engulfed bacteria.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…We have previously found that a mixed culture of Escherichia coli with Tetrahymena ciliates could prove beneficial in gene exchange between the bacteria (Matsuo et al, 2010;Oguri et al, 2011). Since the gene exchanges significantly decline in the presence of phagocytosis inhibitor (latrunculin B), they appear to occur by conjugation via bacterial uptake following accumulation in ciliate vesicles (Matsuo et al, 2010). Thus, our data clearly indicate that ciliate vacuoles provide benefits, via gene exchanges, to the engulfed bacteria.…”
Section: Introductionsupporting
confidence: 50%
“…The bacteria were statically cultured in LB broth containing 1% NaCl, 1% peptone and 0.5% yeast extract at 37°C. The ciliates were also statically maintained in peptone-yeast extract-glucose broth containing 0.75% peptone, 0.75% yeast extract, and 1.5% glucose at 30°C, as described previously (Matsuo et al, 2010). The luminescent bacterium Vibrio harveyi BB170 was used for assessing AI-2 level in the culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L. pneumophila concentration was adjusted by using the optical density method with a spectrophotometer (24). The concentration of protozoa was also determined using the modified trypan blue dye exclusion method (trypan blue assay; trypan blue solution [Sigma] containing 0.6% ethanol stains viable protozoa) (24).…”
Section: Methodsmentioning
confidence: 99%
“…The number of L. pneumophila cells in culture with or without ciliates was assessed by a CFU assay with BCYE agar. Before plating on the agar, the culture of ciliates with bacteria was subjected to bead beating, as described previously (24). The bacterial membrane integrity as a possible indicator for bacterial viability was also confirmed with fluorescence microscopy by using a LIVE/ DEAD reduced-biohazard viability/cytotoxicity kit (Molecular Probes, Eugene, OR) according to the manufacturer's instructions.…”
Section: Assessment Of Lipid Accumulationmentioning
confidence: 99%